Confronting Marginality: human and nonhuman resilience in the landscape of disaster (Altre Modernità, 2022)
The March 2011 Tōhoku triple disaster reinforced an already liminal space inside Japan. The region of Tōhoku, historically considered at the margins, was once again framed as a marginal space separated from the Japanese ‘centre’. However, the physical area of the disaster acquired new figurative dimensions allowing for an artistic and cultural response to the events of March 2011 and to the national narrative of fast recovery. In the novel In the Zone (2016) by Taguchi Randy, the abandoned and marginal landscape of the exclusion zone assumes the characteristics of a space for survival and renovation. The human and nonhuman characters challenge their social and physical marginality through the continuous movement in the exclusion zone and across several physical and figurative boundaries. Furthermore, in this liminal space, bodily acts—such as laughing, dancing, or singing—become a way to build resilience and recover from previous traumas. This paper concludes that the novel In the Zone constructs the disaster as a positive trope engendering recovery from past traumas and confronting national discourses on the environment, women, and marginal communities.
Keywords: nuclear disaster; environmental literature; liminality; women’s writing; Japanese literature; environmental trauma